EVOLUTION OF FAMILY OWNED BUSINESS IN SAUDI ARABIA - Hawraa Zaki Alhashim, Muhammad Khan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The study aimed to understand the evolution of family business in Saudi Arabia. In this study, the primary and secondary data were used. The primary data was collected from first-hand experienced and involved qualitative and quantitative approaches. The primary data was collected through interview and secondary data was collected from books, journals, theses and online website. The interview was conducted with large family owned businesses in Saudi Arabia which helped in understanding of evolution and role of these companies to the country. The samples were included most family businesses in Saudi Arabia who had knowledge and experiences. The sampling method was focused on selected respondent based on top 100 family businesses in Saudi Arabia. The interview showed family owned business made the firm unique in Saudi Arabia. Family owned business were developed and mature and usually last for many generations. Big firms such as Al Zamil group and Al Tamimi group faced several issues and challenges from being family owned in regard to hire non-family members to contribute in the business successful, succession plan and strike a balance between family and business.